2021
DOI: 10.1108/ijoem-02-2020-0205
|View full text |Cite
|
Sign up to set email alerts
|

Optimal combinations of factors influencing the sustainability of Taiwanese firms

Abstract: PurposeThe authors aim to obtain the optimal combinations of factors from institutional environment adaptation mechanisms and internal resources or capabilities that influence the sustainability of a firm.Design/methodology/approachThe authors develop a new index, called the sustainability index, based on the stakeholder perspective by employing a corporate credit risk index, an evaluation of a firm's corporate governance, corporate financial performance and firm age. The authors then apply both Ordinary Least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 73 publications
(87 reference statements)
0
8
0
Order By: Relevance
“…In this sense, in literature it is possible to find that eco-innovation management is a vital function in the survival of manufacturing firms, since this activity allows organizations to adopt activities of collaboration, reconstruction, growth and sustainability (Saleh et al, 2022). IJIEOM 5,3 Lo et al (2021) demonstrated the importance for organizations of the management capacity of eco-innovation in development of long-term sustainable value propositions, which allows manufacturing firms to respond as quickly as possible to the changes that current markets demand (Sakis, 2020;Ivanov, 2020;Correa et al, 2021). Therefore, collaboration plays an essential role in eco-innovation management, since collaboration is usually considered in literature as a great facilitator of organizational agility that helps manufacturing firms to respond both to unforeseen emergencies and to short-term and long-term crises (Wang et al, 2017;Saleh et al, 2022).…”
Section: Collaboration and Management Eco-innovationmentioning
confidence: 99%
“…In this sense, in literature it is possible to find that eco-innovation management is a vital function in the survival of manufacturing firms, since this activity allows organizations to adopt activities of collaboration, reconstruction, growth and sustainability (Saleh et al, 2022). IJIEOM 5,3 Lo et al (2021) demonstrated the importance for organizations of the management capacity of eco-innovation in development of long-term sustainable value propositions, which allows manufacturing firms to respond as quickly as possible to the changes that current markets demand (Sakis, 2020;Ivanov, 2020;Correa et al, 2021). Therefore, collaboration plays an essential role in eco-innovation management, since collaboration is usually considered in literature as a great facilitator of organizational agility that helps manufacturing firms to respond both to unforeseen emergencies and to short-term and long-term crises (Wang et al, 2017;Saleh et al, 2022).…”
Section: Collaboration and Management Eco-innovationmentioning
confidence: 99%
“…PA methodology allows corporations to be proactive, future-orientated, forecast outputs and behaviors based on data and not by assumptions without any supporting data or information. In addition, PA also suggests actionable instructions to benefit users from its predictions (Javaid et al, 2021;Lo et al, 2021). Moving forward, PA will be integrated into business applications and will no longer be a premium domain of mathematicians and statisticians (Dagnino, 2021;Saxena et al, 2021).…”
Section: Predictive Analyticsmentioning
confidence: 99%
“…By using the stakeholder perspective, including firm age, a corporate credit risk index, corporate financial performance and an evaluation of a firm's corporate governance, Lo et al (2021) first develop a new sustainability index. Thereafter, they employ both regression and fuzzy set qualitative comparative analysis (FsQCA) to obtain several models to optimize firms' sustainability.…”
mentioning
confidence: 99%
“…In this special issue, we invite academics and practitioners to submit their research or review manuscripts that fit in the spirit and scope of our special issue. The special issue of Behavioral Financial Economics in Emerging Markets has published five papers including Hong et al (2021), Lo et al (2021), Shen et al (2021), Wong (2021) and Yeap et al (2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation